Quasi-obowiązkowe uczestnictwo w pracowniczych programach emerytalnych na przykładzie Wielkiej Brytanii. Szanse i zagrożenia - Szczepański, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The purpose of this article is to identify the opportunities and threats associated with compulsory or quasi-compulsory participation in occupational pension schemes based on the literature review of the subject and the comparative studies of the effects of introducing such solutions in selected countries (UK, Ireland). On this basis, conclusions and recommendations will be made regarding the proposed introduction of similar solutions in the Polish pension system
Keywords: programy emerytalne; wolontariat; pracownicy